MULTIEDUCULTURALISM IN THE DIGITAL REALM: CYBER CULTURE DEVELOPMENT AND INTEGRATING 4C PERFORMANCE IN EFL LEARNING - Yuliana, Yohanes Gatot Sutapa; Tjan, Farina; Laili, Nurwinda (Journal of English Educational Study (JEES), 2025)
This research reveals how multieducationalism in the digital realm influences the development of cyber culture and the integration of 4C skills (Communication, Critical Thinking, Collaboration, Creativity) in learning English as a Foreign Language (EFL) in the English master's study program. With a basic development design (DDR), this research finds the benefits of digital technology in EFL learning in integrating diverse cultural perspectives and developing important skills needed in the global era based on localized wisdom that is relevant in border areas. This research also reveals the challenges and opportunities faced in this process.